1980
DOI: 10.1080/00288233.1980.10430796
|View full text |Cite
|
Sign up to set email alerts
|

Aerobiology ofSclerotinia sclerotiorumandBotrytis cinereaspores in New Zealand tobacco crops

Abstract: The seasonal abundance of ascos'pore~of Sclerotinia sclerotiorum (Lib.) de Bary m the au depended~n ramfall rnotstenmg the soil sufficiently for apothecia to devt:l~p. No otherclimatic factors were found to be related to the trapping pattern.Conidia of Botrytis ctnerea Pers, ex Fr. were released in large numbers if the preVIOUS day was calm and the night wal"Ill;, or when rain was falling. Few conidia wer~released~t night unless ram was falhng. Ascospores of S. sclerotiorum and conidia of B. ctnerea both showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 5 publications
2
13
0
Order By: Relevance
“…Our results are in agreement with those of Hartill (1980) and Suzui and Kobayashi (1972a), who found that the majority of ascospores of S. sclerotiorum were deposited within a few metres of the source (apothecia). Our results imply that Sclerotinia stem rot of soybean results mainly from ascospores produced within the field.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our results are in agreement with those of Hartill (1980) and Suzui and Kobayashi (1972a), who found that the majority of ascospores of S. sclerotiorum were deposited within a few metres of the source (apothecia). Our results imply that Sclerotinia stem rot of soybean results mainly from ascospores produced within the field.…”
Section: Discussionsupporting
confidence: 83%
“…Hartill (1980) found that ascospores of S. sclerotiorum were trapped in large numbers when apothecia were found near the trap. In sporetrapping studies in sunflower (Helianthus annuus) fields artificially infested with sclerotia of S. sclerotiorum, McCartney and Lacey (1991) concluded that disease severity may be related to the concentration of ascospores during the infection period.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ascospore production was more or less confined to the middle of the day with few spores being released ;it night or in the early morning, a pattern similar to that found by Harthill (1980) in tobacco crops. Thc mechanisms of ascospore release in S. sclerotioririii are not \\.ell known, but changes in humidity i d light have been implicated in XCOSpore discharge in other ascomycetes (Ingold 1971).…”
Section: Discussionmentioning
confidence: 57%
“…1 and 4): in 1988 there were about 450 ascospores m-3 in the air, averaged over 24 h, for every 100 apothecia in the plot, in 1989 the relationship between apothccia and ascospores was less clear but more ascospores per apothecia appeared to have been produced. Harthill (1980) found little relationship be- tween ti,eilther variables and ascospore concentration above tobacco crops in New Zealand as long as there was sufficient rain to moisten the soil and promote apothccia formation.…”
Section: Discussionmentioning
confidence: 99%